Development of 3D printable antibacterial water filters in vertical farms - Pothunuri Laya (Nanyang Technological University, 2022)
“We are what we eat”. And we prefer to consume food that keeps us energetic, healthy, and fit. By 2030, Indoor Urban Vertical Farming (IUVF) which provides fresh, locally grown food, is anticipated to feed the populace in “megacities” [1]. These systems typically employ recirculating water that poses the risk of fresh produce cross-contamination [2]. Potential foodborne diseases and health risks too were identified in associated systems through food safety analyses [3]. Although the detection of hazardous bacteria and pathogens has been done by various research studies, suitable risk management methods are still inadequate. Large-scale farming systems operate under controlled conditions, rendered by numerous sensors and software applications which is impractical to be scaled down for domestic use [4]. So, the use of simple filters was evaluated as a way to improve the microbial quality of irrigation water. This project analyzed the existing water filters for small-scale vertical farms, and the modified material of PLA with ZnO was proposed for manufacturing the filters. Thus, its antibacterial activity against E. coli bacteria present in hydroponic water samples was successfully validated. The filters designs were developed to better address the user needs and were derived from lattice structures. Accordingly, the filter designs were compared based on greater surface area of contact and various other features such as mechanical stress, fluid flow characteristics and 3D printability. Using DMM technique, TPMS-based lattice designs were proven to be more effective than beam-based types for filtration purposes and Lidinoid and Diamond-based lattices were determined as the optimal solutions.